No pain, just gain: Painless, easy, and fast dried blood spot collection from fingertip and upper arm in doping control. Issue 10 (13th August 2021) - Solheim, Sara Amalie; Ringsted, Thomas Kamm; Nordsborg, Nikolai B.; Dehnes, Yvette; Levernæs, Maren Christin Stillesby; Mørkeberg, Jakob
Abstract: This study aimed to determine and compare the perception, painfulness, and usability of the minimally invasive dried blood spot (DBS) collections from fingertip versus upper arm from different athlete populations: males and females representing sports dependent on hand/arm, sports less dependent on hand/arm and para‐athletes. To accomplish this, 108 national level athletes from Denmark were recruited (♀ = 49, ♂ = 59, 25 ± 6 years; mean ± SD) and 11 Doping Control Officers (DCOs) collected manual fingerprick DBS (HemaSpot HF) and automated upper‐arm DBS (Tasso‐M20) from each athlete. Athletes and DCOs responded to questionnaires regarding the perception of sample collection procedures. On a 0–10 scale, the athletes reported a low pain score and a very good general experience for both sampling sites, but following upper‐arm DBS collection, the associated pain was rated lower (−0.4 ± 1.6, p  < 0.05), and the general experience rated better (+0.6 ± 2.3, p  ≤ 0.001) than after the fingerprick DBS collection. The DCOs rated the general experience with the upper‐arm DBS collection better (+1.6 ± 1.1, p  ≤ 0.01) than the fingerprick DBS collection, partly because problems occurred more frequently during the DBS collection from the fingertip (28%) than from the upper arm (6%). In conclusion, it appears that DBS sampling is affiliated with minimal sensation of pain and is preferred by both DCOs and athletes, independent of gender and discipline, over conventional sample collection methods. Collection of DBS from the upper arm was preferred over fingerprick by both athletes and DCOs. Abstract : Several dried blood spot (DBS) collection devices exist, allowing collection of capillary blood from different anatomical sites. In this project, a total of 108 matched DBS samples from the fingertip (HemaSpot HF; lancet device) and the upper arm (Tasso‐M20; microneedle device) were collected to evaluate athletes and doping control officers (DCOs) preferred DBS sample collection site/device in regard to perception, painfulness, and usability.